2013
DOI: 10.1111/ddi.12118
|View full text |Cite
|
Sign up to set email alerts
|

On the front line: integrated habitat mapping for olive ridley sea turtles in the southeast Atlantic

Abstract: Aim Knowledge and understanding of marine vertebrate spatial ecology are required to identify sources of threat and highlight areas for conservation. Olive ridley sea turtles Lepidochelys olivacea are in decline in some regions and data for the Eastern Atlantic are sparse. Here, we seek to describe observed, and potential, post-nesting habitats for this species in the southeast Atlantic. We contextualise these with fisheries catch data to identify areas of potential threat from fisheries interaction for this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 63 publications
0
50
1
1
Order By: Relevance
“…This intense habitat use allows for more targeted conservation measures . Some of the tracked females remained in the area for over a month before switching to the transiting phase and moving south, likely to known foraging grounds off the coast of Angola (Pikesley et al, 2013b). This is the first noted occurrence where olive ridley turtles almost exclusively used estuarine habitat during their internesting period.…”
Section: Internesting Estuarine Movementsmentioning
confidence: 89%
See 2 more Smart Citations
“…This intense habitat use allows for more targeted conservation measures . Some of the tracked females remained in the area for over a month before switching to the transiting phase and moving south, likely to known foraging grounds off the coast of Angola (Pikesley et al, 2013b). This is the first noted occurrence where olive ridley turtles almost exclusively used estuarine habitat during their internesting period.…”
Section: Internesting Estuarine Movementsmentioning
confidence: 89%
“…Turtle P had location points within the internesting period that demonstrated an unexpected full behavioral switch from internesting to transiting then back to internesting. During the switch, the turtle remained in the Komo Estuary and later we saw the anticipated long-term behavioral switch to transiting along with a southward movement toward the foraging grounds (Pikesley et al, 2013b). Therefore, we included the short behavioral change in our internesting period analysis.…”
Section: Satellite Transmitter Deploymentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Atlantic Ocean, the post-nesting movements of olive ridley turtles have only been investigated in the eastern population (Pikesley et al 2013), but data are lacking for the largest population nesting in French Guiana, whose conservation status is highly concerning (Kelle et al 2009, Wallace et al 2011, Plot et al 2012. Considering the high oceanographic dynamism along the coast of French Guiana (Frouin et al 1997, Fromard et al 2004) and the contrasting migration patterns of olive ridleys reported else-where (see above), one may predict a pronounced behavioral plasticity in the migration of olive ridley turtles after they have left their nesting site in French Guiana.…”
Section: Introductionmentioning
confidence: 99%
“…The second possibility is of West African origin, which would result in a northward migration. Nevertheless, the movements involved are still not completely understood (Pikesley et al, 2013), although the south-north African route has already been described for green and loggerhead turtles (Carreras et al, 2011(Carreras et al, , 2014Clusa et al, 2014).…”
Section: Resultsmentioning
confidence: 99%